A examination on personal data protection in metaverse technology in Indonesia: a human rights perspective - Hanita Mayasari (CV. Ius et Ambientis, 2023)
The objective of this study is to elucidate the challenges presented by technological advancements, namely digital metaverse technology, with regard to safeguarding personal data in Indonesia. This study also investigates these issues via the lens of human rights. The research methodology employed in this study encompasses a mixed approach, combining socio-legal and normative research methods. The research findings indicate that there is a pressing need for the safeguarding of personal data in Indonesia, particularly in light of the escalating number of incidents and the advancement of the information technology sector. The significance of metaverse technology should not be underestimated, thereby necessitating a thorough legislative reform to address the associated difficulties. The enactment of the PDP Law represents the initial measure taken by the government to establish a framework for the administration of personal data protection. The active participation of all stakeholders, particularly those in the digital economy industry, is vital in the formulation and implementation of rules. Additionally, it is crucial to adhere to the principles of Data Protection By Design and By Default. The PDP Law encompasses various significant provisions that can be utilised by the Indonesian government to enforce personal data protection measures and impose penal consequences upon those who breach the regulations stipulated within this legislation. The PDP Law serves as a legal framework that holds applicability not only inside national boundaries but also extends to international jurisdictions, particularly in the context of the contemporary metaverse.